Relate North : Culture, Community and Communication - Jokela, Timo; Coutts, Glen; Lapland University Press (Lapland University Press, 2017)
This anthology contains contributions from Canada, England, Finland, Norway, Russia and Scotland. The interrelated themes of ‘culture’, ‘community’ and ‘communication’ formed the basis of the call that was issued to researchers, artists and designers. Drawing on projects and studies from northern countries, Relate North: Culture, Community and Communication explores contemporary practices in arts-based research and knowledge exchange in the fields of art and design. The chapters and visual essays in the book interpret the terms ‘arts’ and ‘design’ broadly to include, for example, crafts, indigenous making, media and product design. Aspects of culture and community are explored through the lens of contemporary arts and design. The contributing authors provide thought-provoking accounts of current practice in art, design and education. Relate North brings together the work of leading scholars to explore issues of contemporary art, design, and arts-based research. The book will be of interest to a wide audience including, for example, practice-based researchers, artists, designers, anthropologists, geographers and social scientists in addition to those with a general interest in Northern and Arctic issues. publishedVersion